Diagnostic Real-Time PCR for Detection of Salmonella in Food - Malorny, Burkhard (American Society for Microbiology, 2004)
A robust 5′ nuclease (TaqMan) real-time PCR was developed and validated in-house for the specific detection of Salmonella in food. The assay used specifically designed primers and a probe target within the ttrRSBCA locus, which is located near the Salmonella pathogenicity island 2 at centisome 30.5. It is required for tetrathionate respiration in Salmonella. The assay correctly identified all 110 Salmonella strains and 87 non-Salmonella strains tested. An internal amplification control, which is coamplified with the same primers as the Salmonella DNA, was also included in the assay. The detection probabilities were 70% when a Salmonella cell suspension containing 10(3) CFU/ml was used as a template in the PCR (5 CFU per reaction) and 100% when a suspension of 10(4) CFU/ml was used. A pre-PCR sample preparation protocol including a preenrichment step in buffered peptone water followed by DNA extraction-purification was applied when 110 various food samples (chicken rinses, minced meat, fish, and raw milk) were investigated for Salmonella. The diagnostic accuracy was shown to be 100% compared to the traditional culture method. The overall analysis time of the PCR method was approximately 24 h, in contrast to 4 to 5 days of analysis time for the traditional culture method. This methodology can contribute to meeting the increasing demand of quality assurance laboratories for standard diagnostic methods. Studies are planned to assess the interlaboratory performance of this diagnostic PCR method.